Congestion probabilities in OFDM wireless networks with compound Poisson arrivals. Issue 4 (1st March 2020) - Panagoulias, Panagiotis I.; Moscholios, Ioannis D.; Sarigiannidis, Panagiotis G.; Logothetis, Michael D.
Abstract : The authors study the downlink of an orthogonal frequency division multiplexing (OFDM) based cell that services calls from different service‐classes with various resource requirements. They assume that calls arrive in the cell as batches according to a compound Poisson process. They consider that the batch size is generally distributed while each call of a batch is treated separately from the other calls of the same batch, according to the complete sharing policy. To determine the most important performance metrics, i.e. congestion probabilities and resource utilisation in this OFDM‐based cell, they model it as a multirate loss model, show that the steady‐state probabilities can be determined via a product form solution (PFS) and propose recursive formulas which reduce the complexity of the calculations. In addition, they study the bandwidth reservation (BR) policy which can be used for the reservation of subcarriers in order to favour service‐classes whose calls have high subcarrier requirements. The existence of the BR policy destroys the PFS of the steady‐state probabilities. However, they show that there exist recursive formulas for the determination of the various performance measures. Simulation verifies the accuracy of the proposed formulas.